How to form a team : five keys to high performance - Kanaga, Kim; Kossler, Michael E. (Report (Center for Creative Leadership), 2001)
One of the first steps to take toward increasing team effectiveness is to pay attention to how the team is formed. You can head off most of the problems that beset teams during the formation stage by setting a clear direction, building organizational support, creating an empowering team design, identifying key relationships, and monitoring external factors. When a team is formed with the five high-performance principles described in this guidebook, it has a head start on achieving success.